Estimation of predicted breeding value in crossbred dairy cattle in a herd in the highlands of Chimborazo, Ecuador - Larrea Izurieta, Carlos Octavio (2020)
The aim of this study was to estimate genetic parameters and predict genetic merit for milk production adjusted to 305 days (PL) in crossbred cattle as selection criteria. Records of productive data was used from 289 purebred and crossbred animals with 349 lactations between 2000 and 2019. To obtain the PL, the incomplete gamma equation proposed by Woods was applied. The statistical and animal models included the random effects: additive genetic, permanent and temporary environments, while the fixed effects were breed composition, lactation and year of initiation of lactation. To analyze the variance components for the calculation of heritability (h2) and repeatability (r) for PL, the VCE v. 6.0 program was used and the breeding values through the animal model using the MTDFRELM software. Eleven inbred animals were reported with a mean inbreeding coefficient of 0.107 ± 0.115. The mean PL was 2972.1 ± 51.1 kg. Differences were found in breed composition (p<0.05), number of lactations and year of initiation of lactation (p<0.01). The h2 was 0.26 ± 0.16 and r was 0.51 ± 0.15. The predicted genetic values for evaluated animals ranged between -241.5 and +266.5 kg of PL, highlighting the trihybrid breed composition between Holstein, Jersey, Monbéliarde and Red Swedish. Most of the breeding values are pronounced from the fourth lactation. It is concluded that the additive genetic effect is moderately heritable, which indicates the feasibility of increasing the PL, through the adequate selection of elite animals.